2013
DOI: 10.1016/j.yexmp.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in HIV-associated nephropathy (HIVAN)

Abstract: MicroRNAs (miRNAs) play a critical role in multiple biological and metabolic processes. Recent studies suggested that miRNAs are critical in the maintenance of glomerular homeostasis in both physiological and pathological states. However, the role of miRNAs in the pathogenesis of HIV-associated nephropathy (HIVAN) has not been studied. In the present study, we have used a microarray-based approach in combination with real-time PCR to profile the miRNA expression patterns in HIV-1 transgenic mice (Tg26). Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The replication defective HIV-1 virus stocks were obtained by cotransfected pNL4-3:ΔG/P-GFP construct and packaging constructs pCMV R8.91 and pMD.G plasmids into 293 T cells as previously described [5]. Briefly, pNL4-3:ΔG/P-GFP construct was produced by reconstruction of pNL4-3 clone, the same proviral construct used to generate Tg26 transgenic mice, by substituting gag/pol genes with GFP reporter gene.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The replication defective HIV-1 virus stocks were obtained by cotransfected pNL4-3:ΔG/P-GFP construct and packaging constructs pCMV R8.91 and pMD.G plasmids into 293 T cells as previously described [5]. Briefly, pNL4-3:ΔG/P-GFP construct was produced by reconstruction of pNL4-3 clone, the same proviral construct used to generate Tg26 transgenic mice, by substituting gag/pol genes with GFP reporter gene.…”
Section: Methodsmentioning
confidence: 99%
“…Profiles of miRNAs expression in kidney diseases, i.e., polycystic kidney disease [26], diabetic nephropathy [18], ischemia reperfusion injury [9], renal cancer [10], hypertensive nephrosclerosis [37] and kidney fibrosis [6,38] have been investigated. Recently, we reported the profile of miRNAs expression in HIV-1 transgenic mice (Tg26) [5], the most frequently used mouse model of HIV-associated nephropathy (HIVAN) [15]. This report suggested that miRNAs had potential to play a role in the pathogenesis of HIVAN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, many C2MC miRNAs were identified to be the major components in the dynamic regulatory network during embryonic development [39], skeletal and cardiac muscle differentiation or function [9,36], angiogenesis [3] and lung development [37]. Studies have also shown that many C2MC miRNAs or their relatives were often among the most significantly-altered miRNAs in responses to multiple types of cellular stresses, which included nutrition deprivation [11], hyperglycemia [3,38], hypertonic stress [16], oxidative stress [43], xenobiotic stress [41], aging [48], cigarette smoke [17,18], septic shock [40] and virus infection [7,28]. Although there were studies showing that a few C2MC miRNAs might act as important ribo-regulators in the control of cell fate decision, cell proliferation, immune responses, cell cycle and apoptosis [9,11,27,32,37,39,49], the exact roles of many more C2MC miRNAs in cellular stress responses and other biological processes were unknown and remained to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…These mice expressed HIV-1 genes abundantly in skin, muscle, tail, and variably in kidneys, intestine, and thymus [30]. The Tg26 mouse line has been widely used as a model of HIV-1-associated nephropathy [31]. However, whether bone marrow cells in Tg26 mice expressed HIV-1 had not previously been investigated.…”
Section: Discussionmentioning
confidence: 99%